The Emotional Balance Status (EBS) Questionnaire: Capturing Nutrition’s Hidden Role in Decision-Making - Georgios Lountzis; Theodosios Palaskas; Georgios Tsimekis; Patty Tampourea (Dialogues in Clinical Neuroscience & Mental Health, 2025)
This study introduces and evaluates the Emotional Balance Status (EBS) Questionnaire, a novel instrument designed to explore the influence of lifestyle and emotional-hormonal dynamics on decision-making processes. Departing from classical rational decision theories, it emphasizes the neurobiological and hormonal foundations of decision-making, asserting that emotional states, influenced by hormones, that on their turn are influenced by lifestyle, habits and nutrition, significantly impact choices. The questionnaire, composed of 69 items divided across five thematic sections, was administered to a sample of 242 Greek managers and employees. Exploratory Factor Analysis (EFA) and Principal Component Analysis (PCA) revealed nine distinct components, of which six demonstrated acceptable reliability. These components link emotional balance, driven by internal and external lifestyle factors, to work-related, personal, and financial decisions. Findings highlight the independence of key variables and the potential for the questionnaire to be refined into a robust diagnostic and research tool. The results underscore the need to consider biochemical and lifestyle influences in understanding decision-making behaviors, offering opportunities for future inquiry in fields ranging from management to health psychology.